Pengaruh Profitabilitas, Biaya Operasional dan Manajemen Laba Terhadap Pajak Penghasilan pada Perusahaan Manufaktur - Made Susilawati; Muhammad Prasha Risfi Silitonga; Nurmahadi; Musran Munizu; Asri Ady Bakri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the effect of profitability, operating costs, and earnings management on income tax in manufacturing companies. The type of data used in this study is secondary data derived from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange. The sampling method used in this study is the purposive sampling method with a total of 156 observation data. The analysis method used in this study is multiple linear regression analysis with SPSS version 25 analysis tools. The results of this study indicate that profitability has a positive and significant effect on tax income. Operating costs have a positive and significant effect on income tax. While earnings management does not have a significant effect on tax income.